Dating Hadits Tentang Persaksian Melihat Hilal: Telaah atas Isnad Cum Matn Analysis Harald Motzki - Abdul Mufid (Millati: Journal of Islamic Studies and Humanities, 2017)
There are many studies of hisab rukyat hadiths, one of them is about the sighting of hilal (new crescent moon). By tracing various of Hadith literatures; pre canonical, canonic, and post canonical, informations are obtained in which pre-canonical collection contains five sources, the canonical collection contains four sources, and the canonical post collection contains six sources, so overall, hadiths about the sighting of hilal are documented in 15 sources. This paper will review the hadiths related to the sighting of hilal by using isnad cum matn analysis introduced by Harald Motzki. This approach is intended to analyze the hadiths authenticity by tracing the origin of the hadiths, especially about the sighting of hilal. Five methods of analysis and classification proposed by Horald Motzki will be used as the main framework of analysis to obtain the findings and conclusions which are representative and accountable. Thus, this article attempts to answer the questions of how the origins of the hadith of the sighting of hilal according to cum matn Harald Motzki’s isnad and how is the implication?